2009
DOI: 10.1016/j.amepre.2009.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Children's Roles in Parents' Diabetes Self-Management

Abstract: Background Family support is important in diabetes self-management. However, children as providers of support have received little attention. This study examines the role of children in their parents’ diabetes self-management, diet, and exercise. Methods This research used community-based participatory research principles. Researchers conducted semi-structured parallel interviews of 24 Latino and African-American adults with diabetes and with a child (age 10–17 years) in their home (2004–06). Interviews were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 37 publications
3
35
1
Order By: Relevance
“…In a qualitative study, Latino and African-American adults with diabetes reported that their children reminded them to do PA, and would initiate joint exercise (Laroche et al, 2009). Currently, it is not clear if children are primarily motivated to encourage their parents to adopt healthy behaviors in response to ill health, or if these findings also extend to children whose parents are in good health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a qualitative study, Latino and African-American adults with diabetes reported that their children reminded them to do PA, and would initiate joint exercise (Laroche et al, 2009). Currently, it is not clear if children are primarily motivated to encourage their parents to adopt healthy behaviors in response to ill health, or if these findings also extend to children whose parents are in good health.…”
Section: Introductionmentioning
confidence: 99%
“…This model proposes that communication about a health threat among family members, followed by a shared appraisal of that threat, may lead to cooperative action to address the health threat (Koehly & Loscalzo, 2009). One interpretation of Laroche et al (2009) finding is that children’s encouragement and co-engagement in PA with ill parents reflects a communal coping process, motivated by the families appraisal of a health threat.…”
Section: Introductionmentioning
confidence: 99%
“…Research assessing chronic disease outcomes and parenthood has shown that parents with diabetes report healthier dietary intake, more physical activity, and more consistent blood sugar monitoring compared with nonparents with diabetes. 6 Overall, there is a paucity of research related to the connection between parenthood and young adult health behaviors. In particular, there are few studies that have examined associations between parenthood and men's health behavior outcomes.…”
mentioning
confidence: 99%
“…The DESMOND trial (17) showed significant change in HbA1C levels in both groups with higher change in the study group (1.49% vs. 1.69%), whereas the difference between the groups was not significant after adjusting for baseline and cluster effect (P = 0.52 at 12 months). The Spanish trial (18,19), which assessed the outcome at 6 months, showed significant improvement in HbA1C levels in the study group with P value = 0.040 after controlling confounders and baseline differences using ANCOVA models. Steinsbekk et al 's (20) review study analyzed 13 studies with 1827 participants with HbA1C levels assessed at 6 months.…”
Section: Discussionmentioning
confidence: 99%